Beyond the Motive: Lessons Learned from Work Commitment Based on Pesantren - Mundiri, Akmal; Najiburrohman, Najiburrohman; Jali, Hasan; Putri, Dinda Febrianti (SCAD Independent, 2026)
Educators’ performance in Pesantren is often measured by the salaries they receive. The salaries of educators and administrative staff at Pesantren are often below the minimum wage. Thus, work motivation arises not from the fulfilment of biological needs, but from the operation of higher values of life’s meaning. This research aimed to understand the forms of pesantren-based work motivation and the factors that shape it. The research employed a qualitative approach with a phenomenological design to explore the forms of motivation rooted in Pesantren values that influence the commitment to work of teaching and educational staff. Data were collected through in-depth interviews, participatory observation, and document analysis in traditional Pesantrens in East Java. Data analysis was carried out using MAXQDA. The research results showed that the forms of Pesantren-based work motivation consisted of ruhul jihad, sincerity of intention, management of responsibility, self-control, and spirit of service. The research results also showed that the factors that form Pesantren-based work motivation consisted of qasd al-Amal (intention to work), vertical and horizontal balance, tabarrukan, career sustainability and job security, and interpersonal connectedness. These values, deeply embedded in the Pesantren environment, contribute to a strong work commitment that is intrinsic and enduring.